Identification and Antibiotic Resistance Edwardsiella tarda from Clown Knifefish (Chitala chitala) in the Mekong Delta, Vietnam - Dung, Tu Thanh; Thi, Quach Van Cao; Trung, Nguyen Bao (Bogor Agricultural University, Indonesia, 2024)
This investigation is intended to isolate, identify, and assess the pathogenicity of Edwardsiella tarda, which originated from diseased clown knifefish. A total of 43 isolates were obtained from infected fish samples in Hau Giang and Dong Thap provinces of the Mekong Delta, Vietnam. Two isolates of DT37 and HG41 were identified as E. tarda by morphological, biochemical, and 16S rRNA gene sequencing. Experimental challenge studies revealed that isolate DT37 leads to 83.33% at a 108 CFU/ml concentration after 60 hours. Meanwhile, in isolate HG41, mortality reached 100% within 48 hours post-injection at the highest concentration of 108 CFU/ml. The challenged clown knifefish exhibited gross signs of abnormal swimming, skin ulcerations, and petechial hemorrhages in the body. Internally, ascites with hemoperitoneum, light-colored nodules on the liver, hemorrhagic kidneys, and splenomegaly were also recorded. The LD50 of two isolates, DT37 and HG41, was 4.89 × 105 and 4.07 × 105 CFU/ml, respectively. The antibiogram result showed that most of the isolates were highly susceptible to ampicillin (65%), enrofloxacin (85%), florfenicol (100%), flumequine (90%), cefotaxime (80%), and trimethoprim and sulfamethoxazole (70%). However, the bacterial isolates were highly resistant to doxycycline (75%) and streptomycin (100%).